2021
DOI: 10.1093/gigascience/giaa142
|View full text |Cite
|
Sign up to set email alerts
|

A new duck genome reveals conserved and convergently evolved chromosome architectures of birds and mammals

Abstract: Background Ducks have a typical avian karyotype that consists of macro- and microchromosomes, but a pair of much less differentiated ZW sex chromosomes compared to chickens. To elucidate the evolution of chromosome architectures between ducks and chickens, and between birds and mammals, we produced a nearly complete chromosomal assembly of a female Pekin duck by combining long-read sequencing and multiplatform scaffolding techniques. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 120 publications
(124 reference statements)
4
45
1
Order By: Relevance
“…S24). Such high trans-contacts between microchromosomes were also found in our companion study on the duck genome (Li et al 2021) and were reported previously for the rattlesnake (Schield et al 2019), as well as for small-sized chromosomes in human cells (Lieberman-Aiden et al 2009), and therefore it is probably a conserved chromosome territorial feature of vertebrates (Perry et al 2020).…”
Section: Microchromosomes Have An Excess Of Interchromosomal Contacts Associated With Housekeeping Genessupporting
confidence: 87%
“…S24). Such high trans-contacts between microchromosomes were also found in our companion study on the duck genome (Li et al 2021) and were reported previously for the rattlesnake (Schield et al 2019), as well as for small-sized chromosomes in human cells (Lieberman-Aiden et al 2009), and therefore it is probably a conserved chromosome territorial feature of vertebrates (Perry et al 2020).…”
Section: Microchromosomes Have An Excess Of Interchromosomal Contacts Associated With Housekeeping Genessupporting
confidence: 87%
“…The majority of the genomes we have used are of this data type. The recent sequencing of avian genomes using multiplatform approaches have resolved gaps present in short read assemblies, finding these gaps to be rich in interspersed, simple, and tandem repeats ( Li et al 2021 ; Peona et al 2021 ). Of particular note, Li et al (2021 ) resolved gaps in the assembly of Anas platyrhynchos which we analyzed here using long-read sequencing, and found the gaps to be dominated by the two CR1 families that have recently expanded in waterfowl (Anseriformes): CR1-J and CR1-X.…”
Section: Discussionmentioning
confidence: 99%
“…The recent sequencing of avian genomes using multiplatform approaches have resolved gaps present in short read assemblies, finding these gaps to be rich in interspersed, simple, and tandem repeats ( Li et al 2021 ; Peona et al 2021 ). Of particular note, Li et al (2021 ) resolved gaps in the assembly of Anas platyrhynchos which we analyzed here using long-read sequencing, and found the gaps to be dominated by the two CR1 families that have recently expanded in waterfowl (Anseriformes): CR1-J and CR1-X. Species with low-quality assemblies may have full-length repeats present in their genome, yet the sequencing technology used prevents the assembly of the repeats and hence detection.…”
Section: Discussionmentioning
confidence: 99%
“…The recent sequencing of avian genomes using multiplatform approaches have resolved gaps present in short read assemblies, finding these gaps to be rich in interspersed, simple and tandem repeats (Peona et al 2021;Li et al 2021). Of particular note (Li et al 2021) resolved gaps in the assembly of Anas platyrhynchos which we analyzed here using long read sequencing, and found the gaps to be dominated by the two CR1 families that have recently expanded in waterfowl (Anseriformes): CR1-J and CR1-X. Species with low quality assemblies may have full length repeats present in their genome, yet the sequencing technology used prevents the assembly of the repeats and hence detection.…”
Section: Genome Assembly Quality Impacts Repeat Identificationmentioning
confidence: 99%
“…The majority of the genomes we have used are of this data type. The recent sequencing of avian genomes using multiplatform approaches have resolved gaps present in short read assemblies, finding these gaps to be rich in interspersed, simple and tandem repeats (Peona et al 2021;Li et al 2021). Of particular note (Li et al 2021) resolved gaps in the assembly of Anas platyrhynchos which we analyzed here using long read sequencing, and found the gaps to be dominated by the two CR1 families that have recently expanded in waterfowl (Anseriformes): CR1-J and CR1-X.…”
Section: Genome Assembly Quality Impacts Repeat Identificationmentioning
confidence: 99%